Pemodelan Perubahan Morfologi Sungai Akibat Pembuangan Lumpur Sidoarjo Pada Kali Porong - Rahman Alam, Rizki Robbi; Saud, Ismail; Ansori, Fakhrudin Naufal; Ralindra, Deris Faisa; Prajitno, A. Faiz Hadi (Jurnal Aplikasi Teknik Sipil, 2024)
The continuous discharge of mud into Porong River can affect the river's capacity. Therefore, this research aims to understand Porong's River capacity after becoming a disposal site for Sidoarjo mud and to analyze its effects over the next 10 years. The methods used include the application of the Thomas Fiering method to generate rainfall data during that period. This rainfall data is then processed using FJ Mock calculations to obtain Kali Porong's discharge data. Subsequently, this river discharge data is input into the MIKE 21 application to simulate the water surface elevation in Kali Porong. The results of this study include modeling of water surface elevations that reveal the distribution of sediment deposited at various locations based on U*. An important implication of this research is that the modeling results can be used by relevant parties in managing Kali Porong's capacity as a disposal site for Sidoarjo mud until 2032. A critical finding from this study is the presence of sections with overtopping conditions on both the right and left sides of line 5, suggesting the need to raise the embankment by 2 meters on the right side and 0.5 meters on the left side to maintain the capacity and sustainability of the river.